A Critical Review of Nuisance Foam Formation and Biological Methods for Foam Management or Elimination in Nutrient Removal Facilities. (1st June 2014) - Parker, Denny; Bratby, John; Esping, Don; Hull, Ted; Kelly, Rick; Melcer, Henryk; Merlo, Rion; Pope, Rod; Shafer, Todd; Wahlberg, Eric; Witzgall, Robert
ABSTRACT: : The classifying selector was introduced to the wastewater industry in 2001, after several successful full‐scale applications. The classifying selector concept distinguishes itself from the earlier surface foam wasting schemes in that negative selection pressure is maintained so that nuisance foam‐causing organisms cannot gain a foothold in sufficient numbers to cause nuisance foams. The propensity of the nuisance‐causing organism to attach to bubbles and establish a rising velocity is used to enrich them in a surface mixed liquor layer, where they are wasted. Neither standard texts nor the Water Environment Federation's Manuals of Practice adequately describe this, and as a result, the benefits of foam elimination obtainable through use of the classifying selector concepts have not been broadly obtained in our industry. In certain types of processes that are inherently foam trapping situations, the only solution is surface foam wasting, as foam cannot be eliminated. Potential efficiency gains possible in these situations are addressed.